The Bible : a biography - Armstrong, Karen, 1944- (London : Atlantic Books, 2007)
Religious historian Armstrong discusses the conception, gestation, life, and afterlife of history's most powerful book. Armstrong analyzes the social and political situation in which oral history turned into written scripture, how this all-pervasive scripture was collected into one work, and how it became accepted as Christianity's sacred text. She explores how "as the pragmatic scientific ethos of modernity took hold, scripture was read for the information that it imparted" and how, in the nineteenth century, historical criticism of the Bible caused greater fear than Darwinism.--From publisher description.
Introduction -- 1. Torah -- 2. Scripture -- 3. Gospel -- 4. Midrash -- 5. Charity -- 6. Lectio divina -- 7. Sola scriptura -- 8. Modernity -- Epilogue -- Glossary of key terms -- Notes -- Index.
Includes bibliographical references (p. [243]-277) and indexes.
Keywords: Bible -- History; Bible -- Influence; Christendom